Switchgrass Biomass Composition Altered by Six Generations of Divergent Breeding for Digestibility. Issue 3 (1st May 2013) - Vogel, K. P.; Mitchell, R. B.; Sarath, G.; Jung, H. G.; Dien, B. S.; Casler, M. D.
ABSTRACT: Biomass composition of switchgrass ( Panicum virgatum L.) can affect its utilization by ruminants and its conversion to liquid fuels in a biorefinery. The objective of this study was to evaluate the effects of six generations of divergent breeding for forage in vitro dry matter digestibility (IVDMD) on switchgrass biomass composition, forage quality traits, and ethanol yield. Initially there was one cycle of selection for both low (C‐1) and high IVDMD (C1 = cv. Trailblazer), followed by four additional breeding cycles for high IVDMD. In cycles 4 and 5, winter survival was included as a selection criterion because of decreased winter survival of the C3 population. The experimental populations that were produced by these breeding generations and nine half‐sib families from cycle 5 were evaluated for two post‐establishment years at the research station in eastern Nebraska, where all the breeding work was conducted. The six breeding generations resulted in significant differences among the populations for all the 28 cell wall and non‐cell‐wall composition variables measured, forage quality, and ethanol yield traits measured except for total biomass C, cell wall concentration, soluble glucose, and etherified ferulates. These traits included all cell wall and nonstructural carbohydrates. Breeding for the heritable complex trait IVDMD affected a large number of plant biomass characteristics and also adversely affected plant biomass yield and winter survival.